Analysis of attitudes towards drug addicts among students of health sciences faculty - Üstüner Top, Fadime; Genç, Hatice; Erkuran, Hatun; Kaymak, Esra; Göllü, Şimal; Aydın Pekdemir, Emine (Journal of Dependence, 2009)
Objective: This study was done to investigate the attitudes assumed by the students of the Faculty of Medical Sciences towards the individuals taking drugs that cause addiction.Method: The population of this research, both descriptive and dimensional, was formed by 305 students attending school in the academic year of 2008- 2009, but the research was able to be completed with the involvement of only 244 (%80) students., In this research were used a questionairre form in which is included students' personal information and an attitude-scale for inviduals taking drugs as the data-gathering tools. The data obtained were evaluated with a packet program 'SPSS 16.O.'Results: 244 students, of whom 97,5 % female and 2,5% male, were involved in the study. The students' average age was found to be 20,59±1,82 (17-31) and their average point on the attitude-scale was found to be 57,23±7,68 (2781). The results obtained indicated that the attitude-score for drug-taking, which the students at Faculty of Medical Sciences got, had a more right- bent disperse than normal. The attitude assumed by the University students towards the individuals who take drugs was found to be at a significant level on the part of mothers' educational level (p
Keywords: Addiction; drugs causing addiction; student; attitude